Workshop Computational Thinking untuk Guru MI NW Gelogor, Kediri, Kabupaten Lombok Barat - Apriani Apriani; Kartarina Kartarina; Miftahul Madani (LPPM Universitas Bumigora, 2022)
This workshop activity aims to provide training for teachers to be able to understand and implement computational thinking in the subjects they teach. The lack of trained personnel and lack of understanding in implementing computational thinking provide an opportunity for Bebras Bureau to contribute. This is in line with the desire of the Minister of Education and Culture Nadiem Makarim to implement computational thinking in the children's education curriculum as a provision for more innovative learning to answer the needs of the industrial era 4.0. Computational thinking is a thinking process in formulating problems and solutions so that they can be represented in a form that can be executed by information processing agents, both human and computer. The implementation of the service was carried out on subject teachers at Madratsah Ibtidaiyah NW Gelogor, West Lombok. The stages of the workshop consisted of preparing coordination with partners, preparing training materials, making questionnaires at the beginning and end of the activity, filling out questionnaires at the beginning of the training, Computational Thinking training for MI teachers and filling out a questionnaire at the end of the activity and Evaluation